2013
DOI: 10.1039/c3ob41417e
|View full text |Cite
|
Sign up to set email alerts
|

Spiro-bicyclo[2.2.2]octane derivatives as paclitaxel mimetics. Synthesis and toxicity evaluation in breast cancer cell lines

Abstract: Paclitaxel is one of the most important anti-cancer agents introduced during the last 20 years. However, the use of paclitaxel is limited by undesirable side effects as well as the development of drug resistance. Here, we report a synthetic strategy towards spiro-bicyclo[2.2.2]octane derivatives, which includes double Michael addition and ring-closing metathesis as key synthetic steps. This strategy was used to synthesize a series of spiro-bicyclic compounds designed to be paclitaxel mimetics, which were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Our results clearly showed that the spiroheterocyclic compounds substituted by isoxazole (3), diazepine (4) and oxazepine (6) significantly reduced the proliferation of MCF-7 and MDA-MB-231 cells in a dose-dependent manner. These results were consistent with other studies demonstrating the cytotoxicity of spiro-bicyclic compounds in human cancer cell lines (5,24). Our data are further supported by another report which demonstrated similar in vivo anticancer potential of a spiro-heterocyclic compound on the development on MCF-7 human breast cancer cells (25).…”
Section: Discussionsupporting
confidence: 93%
“…Our results clearly showed that the spiroheterocyclic compounds substituted by isoxazole (3), diazepine (4) and oxazepine (6) significantly reduced the proliferation of MCF-7 and MDA-MB-231 cells in a dose-dependent manner. These results were consistent with other studies demonstrating the cytotoxicity of spiro-bicyclic compounds in human cancer cell lines (5,24). Our data are further supported by another report which demonstrated similar in vivo anticancer potential of a spiro-heterocyclic compound on the development on MCF-7 human breast cancer cells (25).…”
Section: Discussionsupporting
confidence: 93%
“…Even for a hindered exocyclic aldehyde, diastereoselectivity was modest (Scheme 324). 466 Addition to the hindered βalkoxy aldehyde 822 occurred with low diastereoselectivity, which was established after conversion to the resulting cyclic products by ring-closing metathesis. The aldehyde 822 resembles an aldehyde discussed earlier (Scheme 120).…”
Section: Additions To Carbonyl Groups Attached To Ringsmentioning
confidence: 99%
“…64 A domino of two consecutive Michael additions was used to construct the skeleton 162 of the bicyclo[2.2.2]octane derivative 163, which, by a subsequent ring-closing metathesis, gave the spirocyclohexenone-annelated bicyclo[2.2.2]octane 165 as precursor to paclitaxel mimetics (Scheme 34). 65 These examples demonstrate that ring-closing intramolecular metatheses of various gem-diallyl-or gem-dialkenylcycloalkane and -bicycloalkane derivatives induced by Grubbs catalysts can be successfully employed for one-pot syntheses of valuable, both natural and synthetic spiroannelated carbocycles and carbobicycles with intricate structures.…”
Section: Alkene Metathesis With Grubbs Catalysts In the Synthesis Of ...mentioning
confidence: 98%
“…Scheme 34. Formation of Spirocyclohexenone-Annelated Bicyclo[2.2.2]octanes by Ring-Rearrangement Metathesis (RRM)65 …”
mentioning
confidence: 99%